Aid, Governance, and Private Foreign Investment: Some Puzzling Findings and a Possible Explanation - Philipp Harms; Matthias Lutz (Swiss National Bank, Study Center Gerzensee, 2003)
Does official aid pave the road for private foreign investment or does it suffocate private initiative by diverting resources towards unproductive activities? In this paper we explore this question using data for a large number of developing and emerging economies. Controlling for countries' institutional environment, we find that, evaluated at the mean, the marginal effect of aid on private foreign investment is close to zero. Surprisingly, however, the effect is strictly positive for countries in which private agents face a substantial regulatory burden. After testing the robustness of this result, we offer a theoretical model that is able to rationalize our puzzling observation.
Keywords: F35; F21; O16; O19; 330; Aid; Foreign Direct Investment; Institutions; Auslandsinvestition; Entwicklungshilfe; Investitionspolitik; Subvention; Schätzung; Schwellenländer; Entwicklungsländer; Politische Instabilität